GAMIFICATION IN MEDICAL EDUCATION IN RADIOLOGY THROUGH DIAGRADQUIZ FOR TEACHING PATHOLOGICAL PATTERNS OF THE LUNG PARENCHYMA - Ribeiro, Maria Fernanda Sales Ferreira Caboclo; Possolli, Gabriela Eyng; Ribeiro, Marcelo Pereira (Seven Editora, 2024)
The present research reports the process of development and validation of a digital quiz-type game, composed of radiological images of lung diseases, questions and answers, educational videocast, which allows the user to learn in a playful way the diagnosis including Covid-19, helping the continuing education of physicians at a critical moment for public health in Brazil in the face of the Covid-19 pandemic,  With an increase in the number of cases and deaths, with low availability of serological tests, knowledge of tomographic patterns was imperative for diagnosis. The use of serious games is a strategy to offer digital, integrated and motivating learning, with flexibility of time and space for the construction of knowledge. Through the development of a tool that supports the use of active methodologies in medical education, with the creation of gamified mobile digital technology with immersive learning (Game Based Learning), the following research problem is presented: What is the process to create and validate a quiz-type digital serious game for learning pulmonary tomographic patterns and diagnostic imaging in the context of COVID-19? DiagRadQuiz is a game created in a master's research in Health Sciences Teaching, developed from 2019 to 2021. The game was created from a multidisciplinary team composed of a doctor specializing in radiology and diagnostic imaging, a pedagogue in the area of health technologies and an architect working in programming. It is a serious game for Android smartphones, which aims to assess previous knowledge and teach pathological patterns of the lung parenchyma defined in chest computed tomography. The DiagRadQuiz was validated by information technology specialists (games) and doctors specializing in radiology. All evaluators stated that they would indicate DiagRadQuiz as a pedagogical tool for teaching pathological patterns in tomography prevalent in Emergency Care services, including Covid-19. DOI:https://doi.org/10.56238/sevened2024.037-007